The Effect of Brand Love and Customer Satisfaction on Customer Loyalty for Nyai Mercon Products on TikTok with E-WOM as a Moderating - Mustika Aryanti; Arif, Nina Fapari (Universitas Muhammadiyah Pontianak, 2026)
This research examines the impact of brand love and customer satisfaction on customer loyalty toward Nyai Mercon products on TikTok, with e-WOM serving as a moderating factor. Data were collected from 187 customers who purchased through TikTok Shop using purposive sampling. Analysis using SmartPLS 4.0 with the SEM-PLS method revealed that both brand love and customer satisfaction have a significant impact on loyalty. E-WOM moderates the relationship between brand love and loyalty, but does not moderate the satisfaction–loyalty link. These results highlight the importance of emotional engagement, customer satisfaction, and active online interaction in enhancing the competitiveness of SMEs.